Aplikasi Penjualan Pakaian Dan Tas Pada Rumah Produksi Horo Orly - Nuraini, Rini; , Fatah Yasin,S.T.,M.T (2015)
Sales information system to provide information to handle the sale of products or services produced by a shop. Sales service is particularly important when businesses are increasingly ketat.Horo competition Orly is a store that sells a variety of clothing and bags. So that all activities can run better sales again expected for a computerized system. This study aims to create a computerized sales application using OpenCart as aplikasi.Metode manufacture data collection program used method of observation, interview and literature study. Method of system development using SDLC (System Development Life Cycle). Results of the research is a computer-based information systems sales made using OpenCart that is able to process transaction data in Horo Orly.